The situation of committing criminal offenses by professional participants in proceedings - Sup, Yevhen (Archives of Criminology and Forensic Sciences, 2025)
The scientific understanding of the “crime situation” category is developed in several branches of criminal law knowledge. However, situations of crimes committed by professional participants in proceedings have not yet been carefully considered within the criminal law sciences. The Article Purpose was to define the peculiarities of a situation of committing criminal offenses in the field of justice by professional participants in proceedings. Following the research, it was established that the situation of their commission encompasses and reflects the geographical and spatial characteristics of committing criminally punishable acts, preparing to commit such acts, and/or concealing them (in the narrow sense). A typical peculiarity of the situation in which the criminal offenses under study are committed is that the majority of them are perpetrated under evident circumstances, i.e., in the presence of potential victims and witnesses. Only a few are committed under uncertain circumstances, such as secretly and without victims or witnesses, etc. Therefore, the prospects for subsequent research are to define the peculiarities of a typical trace pattern, which is reflected in the crime situation of the type under study.